Move Better, Sleep Better: A Systematic Literature Review of Physical Activity in Sleep Quality Among People With Chronic Diseases - Meiana Harfika; Puri Wulandari (Science Tech Group, 2026)
Sleep disturbance is one of the most common problems experienced by individuals with chronic diseases and can negatively affect physical health, psychological well-being, and quality of life. Physical activity has been recognized as a non-pharmacological intervention that may improve sleep quality in this population. This systematic literature review aimed to analyze the relationship between physical activity and sleep quality among people with chronic diseases. A systematic search was conducted using electronic databases including Scopus, PubMed, and Dimensions. Articles published in English between 2015 and 2026 were included. The inclusion criteria were studies involving adults with chronic diseases, interventions or measurements related to physical activity, and outcomes assessing sleep quality. Various study designs, including randomized controlled trials, cohort studies, and cross-sectional studies, were reviewed. Data extraction and quality assessment were performed systematically to identify the main findings of the included studies. The review found that regular physical activity was consistently associated with improved sleep quality among individuals with chronic diseases, including diabetes mellitus, cardiovascular disease, hypertension, obesity, chronic respiratory disease, and arthritis. Moderate-intensity activities, including walking, aerobic exercise, yoga, and resistance training, demonstrated positive effects on sleep duration, sleep efficiency, reduced sleep latency, and decreased insomnia symptoms. Several studies also reported that physical activity improved mental health and reduced fatigue, thereby indirectly enhancing sleep quality. However, differences in exercise type, duration, frequency, and patient characteristics influenced the effectiveness of interventions. In conclusion, physical activity appears to be an effective and accessible strategy for improving sleep quality among people with chronic diseases. Integrating regular physical activity into chronic disease management programs may yield significant benefits for both physical and psychological health. Further high-quality longitudinal and experimental studies are recommended to determine the optimal type and intensity of physical activity for improving sleep quality in different chronic disease populations.